Greener Organic Light-emitting Device Technology for Sustainable Development - Vandna Nishal; Priti Rani; Devender Singh (Advancements in Science and Technology: Paving the Way to a Sustainable Future, 2025)
Lightening applications in the world consume more than 15% of the total electricity and also contribute to the emission of greenhouse gases. This will further rise worldwide due to the increasing global population. Solid-state lightning application is more power efficient than conventional lightning sources. Organic Light Emitting Device (OLED) technology has revolutionised the field of display and lighting applications. OLED technology is useful as an energy-saving and environmentally friendly lightning way, as it operates at low driving voltage, has a high resolution, and has high brightness. This technology is more power efficient than incandescent lightening, inorganic light emitting devices and liquid crystal displays. Multilayered OLEDs are constituted of different layers such as electron transport layer, emissive layer, hole transport layer and hole blocking layer. These layers are made up of organic materials which makes the OLED biodegradable. If the world is lighted with all OLED lightning then this technology will be highly beneficial for our environment. Here in this chapter, we are highlighting the OLED applications and their impact on greener environment and sustainability.